Cognition and motor learning in a Parkinson's disease cohort: importance of recall in episodic memory. Issue 14 (30th July 2021) - Chung, Yu-Chen; Fisher, Beth E.; Finley, James M.; Kim, Aram; Petkus, Andrew J.; Schiehser, Dawn M.; Jakowec, Michael W.; Petzinger, Giselle M.
Abstract : Impaired motor learning in individuals with Parkinson's disease is often attributed to deficits in executive function, which serves as an important cognitive process supporting motor learning. However, less is known about the role of other cognitive domains and its association with motor learning in Parkinson's disease. The objective of this study was to investigate the associations between motor learning and multiple domains of cognitive performance in individuals with Parkinson's disease. Twenty-nine participants with Parkinson's disease received comprehensive neuropsychological testing, followed by practice of a bimanual finger sequence task. A retention test of the finger sequence task was completed 24 h later. Hierarchical linear regressions were used to examine the associations between motor learning (acquisition rate and retention) and cognitive performance in five specific cognitive domains, while controlling for age, sex, and years of Parkinson's disease diagnosis. We found that a higher acquisition rate was associated with better episodic memory, specifically better recall in visual episodic memory, in individuals with Parkinson's disease. No significant associations were observed between retention and cognitive performance in any domains. The association between motor acquisition and episodic memory indicates an increased dependency on episodic memory as a potential compensatory cognitive strategy used by individuals with Parkinson's disease during motor learning.